The Politics of Manliness: How MS Glow Constructs a New Standard of Beautiful Man via YouTube Narrative ‘Marshel Widianto and Babe Cabita’ - Hendra Agustian; Atiek Puji Lestari; Annisa Laila Alvi Syahri; Andyka Pratiwi; Elsa Maghfira; Sepia Alfira Purnama Putri (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2022)
This study analyzes the MS Glow for Men advertisement in a YouTube video presenting Marshel Widianto and Babe Cabita, using an instrumental approach of the Branded Content Analysis (BCA) method. The advertisement promotes a different representation of masculinity, featuring men with positive personalities and standard bodies, contrasting with the standard image of athletic men in male grooming product advertisements. This approach highlights how influencers influence audiences through various textual, technical, and kinesthetic modes. The research results indicate that the advertisement successfully alters the audience's perception of masculinity, illustrating that masculinity is not only related to physical attributes but also to personality and character. The positive response from the social media audience signifies the advertisement's success in representing diverse concepts of masculinity. This study contributes theoretically by demonstrating the effectiveness of the instrumental approach in analyzing representations of masculinity. Practically, advertisements of this nature provide opportunities to promote a more inclusive and diverse concept of masculinity in the marketing domain.